Poly(propylene naphthalate-co-propylene 2, 5-thiophenedicarboxylate)s derived from bio-based 2, 5-thiophenedicarboxylic acid (TDCA): Synthesis and properties. (January 2021) - Wang, Guoqiang; Yang, Guitang; Jiang, Min; Wang, Rui; Liang, Yin; Zhou, Guangyuan
Abstract: In this study, a series of poly(propylene naphthalate-co-propylene 2, 5-thiophenedicarboxylate)s (PPNTFs) copolyesters were synthesized. The properties of these copolyesters were fine-tuned using 2, 5-thiophenedicarboxylic acid (TDCA). For example, poly(propylene naphthalate) (PPN) and poly(propylene 2, 5-thiophenedicarboxylate) (PPTF) were semi-crystalline polyesters. However, the melting peaks and melt crystallization peaks in PPNTF23, PPNTF50, and PPNTF76 were not observed because the comonomers destroyed the chains' regularity. With the increase in the TDCA content, the glass transition temperature gradually decreased. PPN, PPTF, and PPNTFs had excellent thermal stability over 350 °C and good ductility ( ε b : 130%–320%). High tensile strength (>57 MPa) was observed in PPN, PPNTF23, PPNTF50, and PPNTF76. However, the lowest tensile strength (45.1 MPa) and the highest elongation at break (320%) were observed in PPTF due to the lowest glass transition temperature (36.1 °C). PPTF and PPNTFs exhibited lower processing temperatures than PPN. Highlights: A series of bio-based copolyesters have been successfully synthesized from TDCA, 2, 6-NDCA and 1, 3-PDO. The effects of composition on microstructure and properties were investigated. With the increase of the TDCA content, the glass transition temperature gradually decreases. PPNTF76 was found to exhibit attractive properties, including good mechanical properties and UV-protection properties.